Application of rapid and simple liquid chromatography method for determination of bioequivalence of generic lamotrigine tablets in healthy Iranian volunteers - Samira Sadat Abolmaali; Ali Mohammad Tamaddon; Soliman Mohammadi Samani (Trends in Pharmaceutical Sciences, 2015)
A simple and rapid chromatography method was developed for determination of lamotrigine in human plasma. The method was used to compare the pharmacokinetic (PK) parameters of 50 mg generic and the reference lamotrigine (Lamictal) tablets in healthy Iranian volunteers. High performance liquid chromatography-ultraviolet method was developed and validated to determine lamotrigine concentration in plasma samples. The method was linear over the range of 0.1 to 15 μg/ml. The accuracy and precision were within the acceptable range. Limits of detection and quantification were calculated 0.06 and 0.10 μg/mL, respectively. A randomized, single-dose, two-period, two-sequence crossover study was carried out in healthy subjects receiving either the test or the reference products in each period. Pharmacokinetic parameters were determined using non-compartmental calculations. In vivo bioequivalency between the generic and the reference product was investigated according to the guidance for industry issued by US Food Drug Administration. AUC0-t, AUC0-∞ and Cmax were calculated for the generic product 12.50±2.76 μg.h/mL, 15.04±3.66 μg.h/mL and 0.38±0.08 μg/mL, respectively. The 90% confidence interval for the test/reference ratios were laid in the range of 0.80-1.25 for the log-transformed PK parameters. The generic product is bioequivalent and can be prescribed by practitioners while indicated, however the AUC and Cmax were lower in Iranian population if compared to the literature, which requires further investigations.